Reconciliation, Forgiveness and Violence in Africa : Biblical, Pastoral and Ethical Perspectives. - Solomons, Demaine (Stellenbosch Theological Journal, 2021)
There is no shortage of scholarly contributions grappling with the key concepts of "reconciliation" and "forgiveness" as it pertains to the African and more poignantly the South African context. These notions have a longstanding, yet, contested history and evokes an array of responses ranging from cheering enthusiasm to utter despondency. This contestation has to be understood in relation to the various forms of historical violence inflicted on the peoples of Africa as well as ongoing debates concerning the need to come to terms with the systemic nature of such violence. For the most part, reconciliation and forgiveness and its seemingly contradictory relationship with violence elicit further debates. The question thus remains: at the intersection of ethics and theology, how does one engage such complexity in a way that is distinct from what we have seen and heard before?